Panduan Transformasi Produk Budaya Menjadi Produk Kreatif Budaya Melalui Model Map (Studi Kasus Topeng Malangan) - Erik Armayuda; Reven Praga Deva (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2019)
Culture is one source of inspiration that will be a key value of product competition in the global market. Indonesia with more than 1,300 different ethnic groups has cultural richness which will be the key differentiator in the global market. As the development of the creative industry, culture becomes an element that has more value. There are so many potential cultural products that can be explored. Each requires a study of different approaches to extracting cultural values ​​in a product. From the skin